INTISARI ANALISIS PERSIAPAN PELAKSANAAN PATIENT SAFETY DI RUANG RAWAT INAP (STUDY KASUS DI RSUD KABUPATEN BIMA) - Erwin Santosa; Arif Budi Wibowo (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
The era of globalization impact very rapidly, in the development of advanced medical technology. These conditions have an impact on medical services is very complex and it is potentially causing the error, so that the necessary improvement of health care quality. Patient safety is one important component in the quality of health care. Improved patient safety is a necessary step to prevent and minimize unwanted incident (KTD). Nurses are one of the health workers who are at the forefront of health care and have a very important role in improving patient safety. To determine attitudes on the analysis of patient safety in the inpatient unit nurse Bima district hospital and in particular to identify the components of patient safety attitudes include climate of team work, working conditions, employment decisions, and some factors that support and hinder patient safety attitudes. The research is descriptive qualitative. Subjects were 3 nurses and 3 patients with interview techniques. Data collection techniques in this study used the analysis of qualitative data. A qualitative data analysis technique is using descriptive analysis techniques to describe the data in the field which were analyzed and concluded. Components of the patient safety attitudes is climate of teamwork that showed lower patient safety attitudes, job satisfaction showed high patient safety attitudes, working conditions showed lower patient safety attitudes, for logistical support in the form of medical equipment are laboratory equipments that still lacking. Components of the patient safety attitudes were high  that  consist  job satisfaction, and the low patient safety attitudes components were the teamwork climate and conditions of employment, because they needed additional medical equipment such as laboratory equipments.